Triglyceride Levels Greater Than 10, 000 mg/dL in a 49-Year-Old Female without Evidence of Pancreatitis. (21st May 2019) - Toor, Anika; Toor, Amit; Khalighi, Koroush; Krishnamurthy, Mahesh
Abstract : We present a rare case of a 49-year-old female with very severe hypertriglyceridemia (HTG) having a total triglyceride (TG) count of > 10, 000 mg/dL in the absence of pancreatitis. Based on literature review, this is one of the highest recorded TG counts in an adult without evidence of pancreatitis. HTG is a common occurrence in clinical practice, but rarely do numbers exceed 2000 mg/dl. It is crucial to evaluate and rapidly lower TG levels to prevent potentially life-threatening complications such as severe pancreatitis. Removal of potential predisposing medications, control of underlying diseases known to cause HTG, and maintenance therapies are essential to prevent reoccurrence.